Case Study of Parental Involvement in PAUD Program in TK IPPA Nurul Haq - Lestari Widaningtyas (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
Parental involvement is parental support for children which has a significant impact on children's learning, academic skills, motivation, and self-esteem. This study aims to determine and describe the involvement of parents in the ECE program at TK IPPA Nurul Haq. The research uses a case study qualitative approach. The research subjects were 8 parents and 1 teacher. Data were collected using interviews, observation, and documentation, and analyzed using Miles and Huberman's interactive analysis. The results showed 1) parental involvement in the form of parenting, communication, volunteering, learning at home, decision making, and collaboration with the community; 2) Factors supporting involvement include awareness and friendly attitude of the school;while the barriers are also awareness and busyness; 3) The benefits of involvement are that parents promote schools, get information on children's development achievements, increase children's motivation and learning achievements; 4) Schools have made various efforts to increase parental involvement in TK IPPA Nurul Haq. It is hoped that in the future, teachers can improve good communication and cooperation, so that more parents will be involved in the earli childhood program;because in the end this involvement will have a good impact on children and schools.